PENGGUNAAN TEKNOLOGI INTERAKTIF UNTUK MENINGKATKAN KEMAMPUAN MENYIMAK SISWA SD - Sugianti, Ni Gusti Ayu Nyoman (Jurnal Sultra Elementary School, 2023)
The use of interactive technology in education has become a major concern in improving students' listening skills, especially at the elementary school level. This study aims to analyze the effectiveness of interactive technology in teaching listening skills, the challenges faced in its implementation, and the impact on students' cognitive development. The results showed that interactive technology can improve students' listening skills, but there are challenges in infrastructure and teacher training that need to be overcome. This study concludes that the integration of interactive technology in basic education needs to be supported by adequate policies and continuous training for educators.